2018
DOI: 10.1007/s40544-017-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear of sand-contaminated lubricated sliding

Abstract: This paper reports a test investigation of friction and wear responses from sand contaminated lubricated sliding. The influence of sand contaminants on wear and friction is characterized. Analyses are completed utilizing segments of piston ring sliding against the cylinder liner. Paraffin oil, with and without sand contaminants, is utilized. The effects of the concentration and particle size of sand are examined.Based on the observations in the present work, we found that friction and wear increase with sand c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
(1 reference statement)
1
11
0
Order By: Relevance
“…However, calcite particles may cause wear in aluminum and copper moving parts. In addition, a larger amount of calcite can block engine oil channels, reduce the thickness of oil films, and consequently increase friction between and wear of engine moving parts [8]. Aluminum particles in the engine oil increased significantly with increasing the silica content ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, calcite particles may cause wear in aluminum and copper moving parts. In addition, a larger amount of calcite can block engine oil channels, reduce the thickness of oil films, and consequently increase friction between and wear of engine moving parts [8]. Aluminum particles in the engine oil increased significantly with increasing the silica content ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The melting point of silica particles is more than combustion temperature, and therefore, silica particles, ranging in diameter from 0.3 to 7 µm, deposit on the cylinder wall (between the piston ring and the cylinder wall), and cause wear in these parts [1]. Ramadan [8] showed that the wear of rings increased with increasing the number of silica particles in engine oil. In other words, in line with the results reported by Macian et al [20] and Zali et al [22], the silica content increased the number of iron, aluminum, and chromium in engine oil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Service life of sealing elements is strongly influenced by abrasive wear. It may have various causes, such as air borne dust, suspended particulates in lubricating oil, wear debris due to excessive abrasion, corrosion by-products, or a rough mating surface [8]. Therefore, it is common for PTFE to exhibit poor abrasion resistance, leading to early failure and leakage in mechanical devices, thus, its application has been limited [9].…”
Section: Introductionmentioning
confidence: 99%